Utilization Of Natural Materials Or Used Materials For Fine Motor Stimulation And Children's Creativity At Al-Berkah Pangirkiran Dolok Kindergarten - Daulay, Irma Sari; Hasibuan, Asmi Zakiah; Hasibuan, Henny Gustina; Nasution, Misri Kholidah; Lubis , Nurdelima (DAS Institute, 2025)
This research is based on the limitations of creative learning media and the low ability of children to cut, paste, fold, and arrange simple shapes. This service activity aims to utilize used materials as a learning medium in stimulating children's fine motor development and creativity at Al-Berkah Pangirkiran Dolok Kindergarten. The method used in this activity is a participatory approach by involving teachers and children through direct practice, mentoring, and evaluation of the work. The results of the activity show that the use of used materials has a positive impact on children's development. As many as 80–83.4% of children showed improved fine motor skills, characterized by the skill of sticking leaf collage, as well as making pencil cases out of aqua and straws creatively. However, there are still around 15-20% of children who need further assistance, especially in collage activities that require high concentration and more fine coordination. Thus, it can be concluded that the use of natural materials and used materials can be an alternative learning medium that is cheap, environmentally friendly, and effective to improve children's fine motor and creativity from an early age. This activity also has a positive impact on teachers and parents to be more creative in utilizing the surrounding environment as a source of children's learning.